(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Glycine-betaine (GB) is an abundant organic material in soil, and the chemolithoautotrophic soil bacterium R. eutropha H16, one of the best bio-technological research models, may involve it in metabolism. The effect of different concentrations of GB (7–300 µmol/mL) on bacterial growth parameters and H2-oxidizing activity of hydrogenases (Hyd) was studied. Stimulation of bacterial growth was registered at GB low concentrations, however, high concentrations have a partial inhibitory effect, in contrast to control (Fructose-Nitrogen medium). Upon GB supplementation, the min and max H2-oxidizing Hyd activity of R. eutropha whole cells were 3.4±0.01 U (g CDW)−1 and 16.4±0.01 U (g CDW)−1, respectively at concentrations of 7 µmol/mL and 300 µmol/mL, while it is absent in the control. These results might be used to develop new approaches to produce oxygen-tolerant Hyd.